Growth of boron nitride films on w‐AlN (0001), 4° off‐cut 4H‐SiC (0001), W (110) and Cr (110) substrates by Chemical Vapor Deposition. Issue 3 (21st January 2016) - Coudurier, Nicolas; Chubarov, Mikhail; Boichot, Raphaël; Mercier, Fréderic; Blanquet, Elisabeth; Reboud, Roman; Lay, Sabine; Crisci, Alexandre; Coindeau, Stéphane; Encinas, Thierry; Pons, Michel
Abstract : This study presents growth of boron nitride on w‐AlN (0001), 4° off‐cut 4H‐SiC (0001), W (110) and Cr (110) substrates by Chemical Vapor Deposition. We obtained t‐BN with interplanar distance close to the one of h‐BN. We interpret this result to be an effect of too high supersaturation in the gas phase (too high growth rate). The necessity for the implementation of pulsed‐CVD and low growth rate to form the h‐BN phase is suggested and discussed. Abstract : Boron Nitride is a promising group 13–group 15 compound material that exhibits various interesting properties like wide band gap, chemical stability, attractive mechanical properties and other. The growth behavior of this material has not been investigated in sufficient details to tailor properties of the resulting films. In this work we present the results on the growth of turbostratic boron nitride (t‐BN) thin films at a relatively high growth rate of 3 μm/h with the aim to investigate the potential use of boron trichloride in combination with ammonia as precursors for growth. Deposition experiments were conducted in a vertical cold wall high temperature chemical vapor deposition reactor in the temperature range 1000°C–1700°C depending on the substrate used. Templates of w‐AlN (0001), 4° off‐cut 4H‐SiC (0001), Cr (110) and W (110) were employed as substrates for the BN growth. As‐grown BN layers were characterized by Scanning Electron Microscopy, X‐Ray Diffraction, Electron Diffraction and Raman Spectroscopy. The results indicate that temperature and N/B ratio have a great influence on the crystallinity of the deposited films. For AlN and SiC substrates, a temperature of 1600°C and N/B ratio in range between 3 and 7.5 were identified as the best parameters for the growth of a 2 μm thick t‐BN layer with a spacing between basal planes of about 3.36 Å compare to the 3.33 Å spacing between basal planes of hexagonal or rhombohedral BN (h‐BN or r‐BN). For Cr and W substrates which have a lower mismatch with h‐BN (1 and 8.8 %), layers of t‐BN were deposited at much lower temperature (1000°C–1150°C) with a spacing between basal planes of 3.5 Å and morphology similar to that observed on SiC substrates. We obtained t‐BN layers with in plane strong disorder but out of plane orientation (c‐axis normal to the surface).